O ensino de Física no novo ensino médio e os processos seletivos para o ensino superior - Simone Aparecida Fernandes (2004)
The promulgation of the National Education Law (LDB, 9394/96) introduced a lot of changes in the organization of the high school in Brazil. The physics teaching compose this instruction degree then it can also be oriented with the propositions of this reform. According with the documents that orient the physics teaching restructuring, this can be focused in a valorization of the knowledge and comprehension of the concepts and interpretation of the phenomena. It also can promote the contextualization as a medium to turn off the apprenticeship significant when it is approximated of the student world and the interdisciplinarity as a form to combine the physical knowledge with the others knowledge. However, after eight years of the promulgation of the LDB, many factors had made difficult the implementation of the reform. We believe that one of these factors are the selective process for the superior education which influence the work that is developed in the high school, mainly, the exams of some traditional Universities. The propose of this work is, through a temporal analysis of the electric circuit questions of the of the physics exams of the UFMG, USP and Unicamp, to raise indications of the adequacy of the selective process of these Universities to that definethe LDB and the National Curricular Parameters orient. We believe also that the implementation of a new physics teaching will be effective if, beyond other factors, these exams will be adequate to it is proposed by the reform so that they contribute for that.